The Lignocellulolytic Activity and Ability to Produce Indole Acetic Acid Hormone of Fungal Inoculant Isolated From Spent Mushroom (Agaricus sp.) Substrate - RADEN HARYO BIMO SETIARTO; IWAN SASKIAWAN (Indonesian Society for microbiology, 2013)
The main problem in soil conservation is the lack of carbon source from organic material. Rice straw from spent mushroom substrate (SMS) can be used as organic fertilizer to supply organic carbon for soil. It can also improve soil structure and increase macro-elements and micro-elements required by plants. This research focused on analyzing lignocellulolytic activity and Indole Acetic Acid (IAA) concentration produced by 14 fungal strains isolated from rice straw that had previously been used as substrate for champignon (Agaricus sp.). Four fungal strains were isolated (JPF 2, JPF 5, JPF 13, and JPF 14) and then characterized. JPF 14 isolate had the highest laccase activity (1.767 U mL-1) and produced the highest concentration of indole acetic acid (IAA) hormone (6.78 mg mL-1). JPF 13 isolate had the highest amylase activity (0.746 U mL-1). JPF 2 isolate had the highest cellulose activity (0.502 U mL-1). JPF 5 isolate had the highest xylanase activity (0.560 U mL-1). Based on their ability to grow on certain pH and temperature, isolate JPF 2 was classified as mesophylic-acidophylic microbe, isolates JPF 5 and JPF 14 were psycrophylic-acidophylic microbes, and isolate JPF 13 was psycrophylic-alkalophylic microbe.